2014
DOI: 10.1038/ejhg.2014.212
|View full text |Cite
|
Sign up to set email alerts
|

A genetic risk score for hypertension associates with the risk of ischemic stroke in a Swedish case–control study

Abstract: Genetic risk scores (GRS), summing up the total effect of several single-nucleotide polymorphisms (SNPs) in genes associated with either coronary risk or cardiovascular risk factors, have been tested for association with ischemic stroke with conflicting results. Recently an association was found between a GRS based on 29 SNPs discovered by genome-wide association studies and hypertension. The aim of our study was to investigate the possible association of the same GRS with ischemic stroke on top of other 'trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 48 publications
0
22
0
1
Order By: Relevance
“…The GRS is a multi-locus profile used to transpose the discoveries from candidate gene studies and GWASs into population health tools (Belsky et al, 2013;Fava et al, 2014). A GRS summarizes the effect of multiple variants in a quantitative manner and hence is superior over the predictive power of a single SNP.…”
Section: Cad Is a Multifactorial Disorder And Arises From An Interactmentioning
confidence: 99%
“…The GRS is a multi-locus profile used to transpose the discoveries from candidate gene studies and GWASs into population health tools (Belsky et al, 2013;Fava et al, 2014). A GRS summarizes the effect of multiple variants in a quantitative manner and hence is superior over the predictive power of a single SNP.…”
Section: Cad Is a Multifactorial Disorder And Arises From An Interactmentioning
confidence: 99%
“…However, it is not the more significant results you will get when adjusting for more factors. A study had showed that when they adjusted for more factors, the association was somewhat attenuated (21) .…”
Section: Discussionmentioning
confidence: 99%
“…To combine the relatively small effects of individual SNP and to better capture the complex relationship between genetics and the folic acid efficacy, the use of genetic risk score (GRS) has been proposed. There are two common approaches that can be used to determine the genetic risk based on risk-related SNP: (a) simple count genetic risk score (SC-GRS) and (b) weighted genetic risk score (wGRS) (20)(21)(22)(23) .…”
mentioning
confidence: 99%
“…The uGRS was generated by summing the number of risk alleles of each SNP (0, 1 or 2). The wGRS was calculated as published by Fava et al (). We summarized beta coefficients for SBP using previous blood pressure GWASs (Ehret et al, , ; Kato et al, ; Liu et al, ; Lu et al, ; Surendran et al, ; Wain et al, ).…”
Section: Methodsmentioning
confidence: 99%